Enhancing Wastewater Treatment with Aerobic Granular Sludge: Impacts of Tetracycline Pressure on Microbial Dynamics and Structural Stability - Shengyan Zheng; Bichen Lou; Zhonghui Yang; Dong Ou; Ning Ai (Microorganisms, 2024)
This study evaluated the efficiency of aerobic granular sludge (AGS) technology in treating wastewater contaminated with tetracycline (TC), a common antibiotic. AGS was cultivated under a TC pressure gradient ranging from 5 mg/L to 15 mg/L and compared with conventional wastewater conditions. The results demonstrated that AGS achieved high removal efficiencies and exhibited robust sedimentation performance, with significant differences in average particle sizes observed under both conditions (618.6 μm in TC conditions vs. 456.4 μm in conventional conditions). Importantly, exposure to TC was found to alter the composition and production of extracellular polymeric substances (EPSs), thereby enhancing the structural integrity and functional stability of the AGS. Additionally, the selective pressure of TC induced shifts in the microbial community composition; Rhodanobacter played a crucial role in EPS production and biological aggregation, enhancing the structural integrity and metabolic stability of AGS, while Candida tropicalis demonstrated remarkable resilience and efficiency in nutrient removal under stressful environmental conditions. These findings underscore the potential of AGS technology as a promising solution for advancing wastewater treatment methods, thus contributing to environmental protection and sustainability amid growing concerns over antibiotic contamination.